Cost-effectiveness analysis of percutaneous coronary intervention for single-vessel coronary artery disease: an economic evaluation of the ORBITA trial. Issue 2 (9th February 2021) - McCreanor, Victoria; Nowbar, Alexandra; Rajkumar, Christopher; Barnett, Adrian G; Francis, Darrel; Graves, Nicholas; Boden, William E; Weintraub, William S; Al-Lamee, Rasha; Parsonage, William A
Abstract : Objective: To evaluate the cost-effectiveness of percutaneous coronary intervention (PCI) compared with placebo in patients with single-vessel coronary artery disease and angina despite anti-anginal therapy. Design: A cost-effectiveness analysis comparing PCI with placebo. A Markov model was used to measure incremental cost-effectiveness, in cost per quality-adjusted life-years (QALYs) gained, over 12 months. Health utility weights were estimated using responses to the EuroQol 5-level questionnaire, from the Objective Randomised Blinded Investigation with optimal medical Therapy of Angioplasty in stable angina trial and UK preference weights. Costs of procedures and follow-up consultations were derived from Healthcare Resource Group reference costs and drug costs from the National Health Service (NHS) drug tariff. Probabilistic sensitivity analysis was undertaken to test the robustness of results to parameter uncertainty. Scenario analyses were performed to test the effect on results of reduced pharmaceutical costs in patients undergoing PCI, and the effect of patients crossing over from placebo to PCI due to refractory angina within 12 months. Setting: Five UK NHS hospitals. Participants: 200 adult patients with stable angina and angiographically severe single-vessel coronary artery disease on anti-anginal therapy. Interventions: At recruitment, patients received 6 weeks of optimisation of medical therapy for angina after which they were randomised to PCI or a placebo procedure. Outcome measures: Incremental cost-effectiveness ratio (ICER) expressed as cost (in £) per QALY gained for PCI compared with placebo. Results: The estimated ICER is £90 218/QALY gained when using PCI compared with placebo in patients receiving medical treatment for angina due to single-vessel coronary artery disease. Results were robust under sensitivity analyses. Conclusions: The ICER for PCI compared with placebo, in patients with single-vessel coronary artery disease and angina on anti-anginal medication, exceeds the threshold of £30 000 used by the National Institute of Health and Care Excellence when undertaking health technology assessment for the NHS context. Trial registration: The ORBITA study is registered with ClinicalTrials.gov, number NCT02062593 .